O POZYCJI PRAWNEJ LUDZI. 5 TYTUŁ 1 KSIĘGI DIGESTÓW. TEKST – TŁUMACZENIE – KOMENTARZ - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
O POZYCJI PRAWNEJ LUDZI. 5 TYTUŁ 1 KSIĘGI DIGESTÓW. TEKST – TŁUMACZENIE – KOMENTARZ